THE RIGHTS OF DIVERSION IN THE CHILDREN’S CRIMINAL JURISDICTION SYSTEM AS THE INTENT OF LEGAL PROTETION - Mustakim Mahmud (Indonesia Prime, 2020)
Child abuse is a complex problem and involves many aspects. Diversion is an alternative in resolving child criminal cases that conflict with the law, by trying to eliminate the stigma against children as perpetrators of crime even though children are in conflict with the law, but still prioritizing the best interests of children in realizing the welfare of children, as stipulated in the SPPA Law . Even though it has been stipulated in written regulations, the existence of diversion among law enforcement officers is still a problem, because the diversion process has not been explicitly regulated regarding the mechanism that must be implemented, so that a good understanding and application is needed by law enforcement officials to be able to actualize properly. the diversion of children in conflict with the law in the juvenile justice system is the implementation of a system in the restorative jusctice to provide justice and legal protection to children in conflict with the law without neglecting the criminal liability of children. Diversion is not a peaceful effort between children in conflict with the law with victims or their families but a form of punishment against children who are in conflict with the law in an informal way. Implementation of diversion in restorative justice in the juvenile justice system is the transfer of the settlement of child cases from criminal justice processes to processes outside of fair criminal justice with an emphasis on restoration to its original state, and not of retaliation. Besides diversion is a form of punishment which has the perspective of education of children. The solution that can be done in overcoming the problem of child problems is that it is expected that in resolving child criminal cases, law enforcement officials should seek diversion in order to restore a balanced harmonization between the perpetrators, victims and the community. Appropriate, considering that crimes committed by children are also increasingly complex, as well as to related parties (Law Enforcement, KPAI, etc.). Massive socialization is needed regarding diversion to the public.